Development of effective hematopoietic stem cell freezing protocols - Perepelytsina, Olena; Kopiak, Bohdan; Yastrebova, Olena; Sydorenko, Mykhailo (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):304